First-in-human phase I study of immunomodulatory E7046, an antagonist of PGE2-receptor E-type 4 (EP4), in patients with advanced cancers. Issue 1 (17th June 2020) - Hong, David S; Parikh, Aparna; Shapiro, Geoffrey I; Varga, Andrea; Naing, Aung; Meric-Bernstam, Funda; Ataman, Özlem; Reyderman, Larisa; Binder, Terri A; Ren, Min; Liu, Mingjie; Dayal, Satish; et al.
Abstract : Background: E7046 is a highly selective, small-molecule antagonist of the E-type prostanoid receptor 4 (EP4) for prostaglandin E2, an immunosuppressive mediator of the tumor immune microenvironment. This first-in-human phase 1 study assessed the safety, tolerability, pharmacokinetics, pharmacodynamics, maximum tolerated dose (MTD) and recommended phase 2 dose of E7046. Methods: This first-in-human study enrolled 30 patients with advanced tumors of cancer types associated with high levels of myeloid infiltrates. E7046 was administered orally once-daily in sequential escalating dose cohorts (125, 250, 500, and 750 mg) with ≥6 patients per cohort. Tumor assessments were performed every 6 weeks. Paired tumor biopsies and blood samples, before and on treatment, were collected for pharmacokinetic and pharmacodynamic characterization of the treatment. Results: No dose-limiting toxicities were observed, and the MTD was not reached. E7046 had an elimination half-life (t1/2 ) of 12 hours, and drug exposure increased dose-dependently from 125 to 500 mg. Target modulation by E7046 was supported by changes in genes downstream of EP4 with concurrent enhanced antitumoral immune responses. A best response of stable disease (per irRECIST) was reported in 23% of patients treated with E7046 (n=30) (125 mg: n=2; 250 mg: n=2; 750 mg: n=3). Over half (4/7) of the patients with stable disease had treatment duration of 18 weeks or more, and three patients (3/15; 20%) achieved metabolic responses. Conclusions: In this first-in-human study, E7046 administered orally once daily demonstrated manageable tolerability, immunomodulatory effects, and a best response of stable disease (≥18 weeks) in several heavily pretreated patients with advanced malignancies. The 250 and 500 mg doses are proposed for further development in the combination setting. Trial registration number: NCT02540291 .